Multiplication of native endomycorrhizae isolated from arid soils on organic substrates in wheat plants ( Triticum aestivum) - José Rafael Paredes-Jácome; Rosalinda Mendoza-Villarreal; Roberto Chiquito-Contreras; Luis Hernandez-Montiel; Valentín Robledo-Torres; Homero Ramírez-Rodríguez (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Organic residues of coffee pulp, sugarcane bagasse and mature bovine manure are a source of organic matter and nutrients for the multiplication of endomycorrhizae consortia. Therefore, the purpose of this research is to multiply the AMFs in such substrates to decrease soil and water pollution.Method A pot experiment under greenhouse conditions was conducted in order to evaluate the influence of agricultural residues (C2-GEC, C3-PAR, C12-PRO, C14-ZAR) with different genera of endomycorrhizae isolated from semi-arid soils, 75 days after the crop was established. Agronomic characteristics and mineral content of N, K, Ca, Mg, and Fe in root and shoot were evaluated in wheat (Triticum aestivum).Results Multiplication of endomycorrhizae was influenced by the residue type. Greater production of spores was observed in the coffee pulp, followed by the sugarcane bagasse, where a higher colonization was obtained in combination of C2-GEC and C3-PAR consortia. This consortia combination also was one of those that have increased the content of N, K, Ca, Mg, and Fe in roots and shoots of wheat.Conclusion Combination of native endomycorrhiza substrates and consortia provides an alternative tool that benefits the physiology and nutrition of the plant to be used in sustainable agricultural production systems.